Constraints facing rural poultry production in PNG: The role of input suppliers - Fang, Peixun; Benny, Dickson; Ovah, Raywin; Roberts, Arthur; Schmidt, Emily; Solomon, Elly (International Food Policy Research Institute, 2023)
Context: The average consumption of protein foods in Papua New Guinea (PNG) remains insufficient to meet nutritious diet guidelines, especially in rural areas. While an expanding literature has demonstrated that poultry is a cost-efficient animal source food to increase protein intake, rural households in PNG face high prices at the market for poultry meat. Similarly, the high price of poultry production inputs constrains greater uptake of rural poultry production. PNG’s heavy reliance on feed (and feed input) imports, as well as high transportation costs and insufficient rural manufacturing and processing infrastructure creates limited opportunities for rural subsistence and commercial poultry production growth. Objective: There is a lack of value chain studies to understand the feasibility of expanding the local mini livestock feed mill model in PNG to increase poultry feed supply in underserved areas. This study builds from earlier work on rural livestock feed infrastructure programs, and aims to fill the knowledge gap on the opportunities and constraints for expanding domestic livestock feed production and distribution via rural mini feed mills. Method: The International Food Policy Research Institute (IFPRI) and the National Agriculture Research Institute (NARI) conducted in-depth qualitative interviews with 8 mini mills and 13 poultry farmers across 4 highland provinces during October and November 2022. We synthesize the interview transcriptions of the qualitative interviews in tandem with quantitative analysis of food consumption and agri-food trade data, as well as the authors’ own field observations in this paper. Results: The in-depth interviews showed that the poultry farmers who purchased from local mini feed mills substantially lowered their feed costs, resulting in greater gross profits compared to rural poultry farmers that only sourced feed from commercial feed suppliers. However, the mini feed mills that we interviewed outlined a series of challenges in sustaining rural feed mills in PNG. The main challenges of running a successful mill included feed mill equipment procurement, electricity reliability, reliable raw ingredient supply, mini mill retailing to secure a client base, and adequate information about feed formulation. We identified two potential approaches that have overcome many of the identified challenges, that could be replicated and adapted to expand mini feed mill operations in the Highlands. The first approach is a farmer cooperative model that incorporates credit and feed delivery services to cooperative farmers. In doing so, they are able to better estimate volume demand for processed feed and accommodate feed production accordingly. The second approach follows a lead firm model, whereby a local farm supply retail outlet is expanding its business to include livestock feed production and supply, overcoming equipment procurement constraints given their previously developed business model focused on farm implement supply. Our evaluation provides detailed costs and benefits of both approaches for potential expansion of these livestock feed producer and distributor models.